Anaplastic ganglioglioma—A diagnosis comprising several distinct tumour types. (16th September 2022) - Reinhardt, Annekathrin; Pfister, Kristin; Schrimpf, Daniel; Stichel, Damian; Sahm, Felix; Reuss, David E.; Capper, David; Wefers, Annika K.; Ebrahimi, Azadeh; Sill, Martin; Felsberg, Joerg; Reifenberger, Guido; et al.
Abstract: Aims: Anaplastic ganglioglioma is a rare tumour, and diagnosis has been based on histological criteria. The 5th edition of the World Health Organization Classification of Tumours of the Central Nervous System (CNS WHO) does not list anaplastic ganglioglioma as a distinct diagnosis due to lack of molecular data in previous publications. We retrospectively compiled a cohort of 54 histologically diagnosed anaplastic gangliogliomas to explore whether the molecular profiles of these tumours represent a separate type or resolve into other entities. Methods: Samples were subjected to histological review, desoxyribonucleic acid (DNA) methylation profiling and next‐generation sequencing. Morphological and molecular data were summarised to an integrated diagnosis. Results: The majority of tumours designated as anaplastic gangliogliomas resolved into other CNS WHO diagnoses, most commonly pleomorphic xanthoastrocytoma (16/54), glioblastoma, isocitrate dehydrogenase protein (IDH) wild type and diffuse paediatric‐type high‐grade glioma, H3 wild type and IDH wild type (11 and 2/54), followed by low‐grade glial or glioneuronal tumours including pilocytic astrocytoma, dysembryoplastic neuroepithelial tumour and diffuse leptomeningeal glioneuronal tumour (5/54), IDH mutant astrocytoma (4/54) and others (6/54). A subset of tumours (10/54) was not assignable to a CNS WHO diagnosis, and common molecular profiles pointing to a separate entity were not evident. Conclusions: In summary, we show that tumours histologically diagnosed as anaplastic ganglioglioma comprise a wide spectrum of CNS WHO tumour types with different prognostic and therapeutic implications. We therefore suggest assigning this designation with caution and recommend comprehensive molecular workup. Abstract : In this study, we undertook comprehensive histological and molecular re‐evaluation of 54 tumours designated as anaplastic ganglioglioma: the majority of these tumours resolved into other CNS WHO diagnoses, most commonly pleomorphic xanthoastrocytoma and glioblastoma. Albeit a small fraction of tumours remained unclassifiable, common features suggesting a separate entity were not obvious. Our results therefore suggest to assign the designation anaplastic ganglioglioma with caution. Comprehensive molecular workup for the differential diagnosis of these tumours is recommended.